Resonant Frequency Calculation and Optimal Design of Peano Fractal Antenna for Partial Discharge Detection - Jian Li; Changkui Cheng; Lianwei Bao; Tianyan Jiang (International Journal of Antennas and Propagation)
Ultra-high-frequency (UHF) approaches have caught increasing attention recently and have been considered as a promising technology for online monitoring partial discharge (PD) signals. This paper presents a Peano fractal antenna for UHF PD online monitoring of transformer with small size and multiband. The approximate formula for calculating the first resonant frequency of the Peano fractal antenna is presented. The results show that the first resonant frequency of the Peano fractal antenna is smaller than the Hilbert fractal antenna when the outer dimensions are equivalent approximately. The optimal geometric parameters of the antenna were obtained through simulation. Actual PD experiments had been carried out for two typically artificial insulation defect models, while the proposed antenna and the existing Hilbert antenna were both used for the PD measurement. The experimental results show that Peano fractal antenna is qualified for PD online UHF monitoring and a little more suitable than the Hilbert fractal antenna for pattern recognition by analyzing the waveforms of detected UHF PD signals.